The specific role of the transformational leadership in the organizational culture of service organizations - Bojana Sokolović; Ivana Katić; Leposava Grubić Nešić; Andrea Ivanišević; Aleksandra Pavlović (Anali Ekonomskog fakulteta u Subotici, 2022)
Transformational leadership links the creative thinking, persistance and energy, intuition and the sense for peoples need for organizational culture. It strives for inovations and expresses the sense for vision and meaning. Literature analysis in this field is followed by the research that examines transformational leadership and its coherance with an organisational culture in the international service company operatig in Serbia. The participants, in his research,  have perceived the role culture as primary , particulary the culture of rules and procedures. This culture is suitable to people that expect security at work, which could be the main goal in the particular company, having in mind that work instability and insecurity have been a common denominator in the past three decades. However, If company wants to be inovative It would have to put more effort into transformational leadership that could not be thorougly examined in this study. Suggestions for further investigations are given at the end of this study , lack of instruments for investigations are pointed out, with an idea for improvements.